Women's Struggle on Men's Heriditary Land Ownership in Minangkabau - Yuhelna, Yuhelna; Isnaini, Isnaini; Wahyuni, Yanti Sri (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2017)
The excavation Galian C in Nagari in Gunung Sarik sub-district have polluted environment and created land conflicts. Women who joined the Gunung Sarik Saiyo cooperative were accompanied by an NGO to carry out a strategy to stop activities that could challenge the social structure of the community. This study aims to describe the strategy of the women in Gunung Sarik sub-district, Padang city. This study used qualitative method with in-depth interview and focus group discussion. The informants were selected by purposive sampling. Female members of Gunung Sarik Saiyo Cooperative struggle for their causes by doing several things. First, affecting ninik mamak (tribal leaders) not to sell their customary land. Second, petitioning their disagreement against excavation Galian C and the sale of customary land. Third, suggesting pro-Galian-C women to reject the activity. The women’s strategy contributes to the decrease of excavation Galian C activity and the improvement of women’s bergaining position in Gunung Sarik sub-district. Keywords: women's strategy, customary land, land conflict Abstrak Adanya Galian C di Nagari di Kelurahan Gunung Sarik membuat tercemarnya lingkungan dan konflik tanah. Perempuan yang tergabung dalam koperasi Gunung Sarik Saiyo didam-pingi oleh LSM untuk melakukan strategi untuk menghentikan kegiatan yang dapat merusak struktur sosial masyarakat. Penelitian ini bertujuan untuk mendeskripsikan bentuk strategi perempuan di kelurahan Gunung Sarik, Kota Padang. Metode yang digunakan dalam penelitian ini adalah metode kuliatatif dengan menggunakan wawancara mendalam dan diskusi grup terfokus dengan informan yang diambil secara purposive sampling. Perempuan yang tergabung dalam Koperasi Gunung Sarik Saiyo melakukan perjuangan dengan melakukan beberapa hal. Pertama, mempengaruhi ninik mamak agar tidak menjual tanah ulayat mereka. Kedua, membuat petisi ketidaksetujuan mereka terhadap galian C dan penjualan tanah. Ketiga, mengajak perempuan yang mendukung galian C untuk tidak mendukung kegiatan tersebut. Strategi yang dilakukan oleh perempuan berkontribusi pada terjadinya pengurangan aktifitas galian C dan bertambahnya bergaining position perempuan di Kelurahan Gunung Sarik. Kata kunci: strategi perempuan, tanah ulayat, konflik tanah